Preparation and characterization of electrodeposited cadmium telluride thin film - Md Daud, Mohd Norizam (2011)
The electrophoretic deposition (EPD) is the most potential techniques in fabricating low cost photovoltaic cells. In preparing CdTe film by EPD technique two factors play a role in determining the suitability and film thickness, i.e. bath temperature and CdTe colloid concentration. Previously, both of these factors were fixed, or with only one factor varied. Here the attempt is made to vary both of these factors in this EPD technique. For this aim, different type of CdTe films were developed from various CdTe colloid concentrations. These concentrations were obtained by mixing 1 to 4.wt% of CdTe powder to the 10.ml solution of equal mixture of methanol and toluene, and deposited at various bath temperatures from 30 to 60.oC. The CdTe thin films obtained are polycrystalline nature of zinc-blend structure with the (111) orientation as the most prominent peak revealed from the XRD analysis. As the CdTe colloid concentration and bath temperature increase the crystallite size of the film, in nano-size, increases and this affects the decrease in micro-strain and dislocation density hence decreases the lattice defect. The transmittance spectra of CdTe thin films shows slightly shift towards longer wavelength which agrees with the decrease of band gap energy with increasing of CdTe concentration and bath temperature for all films. The decrease of band gap energy is due to the increase in nano-crystallite size and the decrease in strain and dislocation density. Here band gap energy of nano-size is greater than that of bulk CdTe (1.44 eV). The CdTe thin film prepared at bath temperature of 30.oC and concentration of 3.wt% using EPD technique was found most suitable for the solar cell application because of the uniform surface, suitable band gap energy, 1.485.eV, and suitable thickness around 8.m. The surface morphology and thickness of the films were determined by AFM analysis. The film thickness increases with CdTe colloid concentration and increases with bath temperature. The increase of the thickness causes the increase of film surface roughness due to the larger crystallite size with increase of concentrations and bath temperatures. The established numerical expression for film thickness with respect to CdTe solution concentrations and bath temperatures agrees well with other literature work.